Genetic mapping in crop plants - Temesgen Begna; Husen Yesuf (Open Journal of Plant Science - Peertechz Publications, 2021)
The genetic map is the chromosome linear linkage map that uses the chromosome recombination and exchange rate as the relative length and genetic markers as the main body. Genetic-map construction is a critically important tool for further genomic studies, as well as for genetic breeding of economically important species. Linkage maps are estimates of the distance between two genetic loci, based on the frequency of recombination. A genetic linkage map with high density and resolution is a critical and indispensable tool in a wide range of genetic and genomic researches. Highly saturated genetic linkage maps are extremely helpful to breeders and are an essential prerequisite for many biological applications such as the identification of marker-trait associations, mapping Quantitative Trait Loci (QTL), candidate gene identification, development of molecular markers for Marker-Assisted Selection (MAS) and comparative genetic studies. Molecular markers are the basis for high-resolution genetic linkage map construction and Quantitative Trait Loci (QTL) fine-mapping, which provide powerful tools for genetic analyses of economic traits. With the rapid development of the biotechnology, dominant DNA markers were gradually replaced by co-dominant markers in genetic mapping including Single Nucleotide Polymorphisms (SNPs) and microsatellites (SSRs). The research area of Association Mapping (AM) is currently receiving major attention for genetic studies of quantitative traits in all major crops. With the development of molecular marker technology in the 1980s, the fate of plant breeding has changed. Different types of molecular markers have been developed and advancement in sequencing technologies has geared crop improvement. Genetic mapping uses the Mendelian principles of segregation and recombination to determine the relative proximity of DNA markers along the chromosomes of an organism. The progress made in molecular plant breeding, genetics, genomic selection and genome editing has contributed to a more comprehensive understanding of molecular markers and provided deeper insights into the diversity available for crops and greatly complemented breeding stratagems. Genetic markers are important developments in the field of plant breeding. The genetic marker is a gene or DNA sequence with a known chromosome location controlling a particular gene or trait. Genetic markers are closely related with the target gene and they act as sign or flags.